2022
DOI: 10.3389/fvets.2022.960865
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A and fibrinogen as markers for early detection of surgical site infection associated with internal fixation in the horse

Abstract: The objective of this study was to determine the diagnostic ability of serum amyloid A (SAA) and fibrinogen for early detection of surgical site infection (SSI) after equine internal fixation. Horses undergoing internal fixation for fracture, arthrodesis, or osteotomy with internal fixation for limb deformity were included in the study. SAA and fibrinogen were measured on blood samples preoperatively and on days 1, 3, 5, 7, 10, and 14 postoperatively. Statistical analysis included use of Spearman's rank correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Serial monitoring of blood SAA can be used to effectively monitor response to treatment (Haltmayer et al, 2017). Thurston et al (2022) also found that serial monitoring of fibrinogen and SAA can be successfully used to monitor horses for development of infection following internal fixation of long bones.…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Serial monitoring of blood SAA can be used to effectively monitor response to treatment (Haltmayer et al, 2017). Thurston et al (2022) also found that serial monitoring of fibrinogen and SAA can be successfully used to monitor horses for development of infection following internal fixation of long bones.…”
Section: Diagnosismentioning
confidence: 99%
“…Minocycline should be considered for treatment of synovial infections due to accumulation of the drug in synovial fluid (Schnabel et al, 2012). Recent investigations indicate the reliability of serial serum amyloid A (SAA) monitoring as a predictor for surgical site infection in cases of fracture, arthrodesis or osteotomy (Thurston et al, 2022). Observance of a decreasing SAA by 1 week post operatively has been correlated with a lower likelihood for developing a surgical site infection and an indication to cease systemic antimicrobial therapy (Thurston et al, 2022).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation